2010
DOI: 10.1007/s00701-010-0761-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lung-protective permissive hypercapnia in intracerebral pressure in patients with subarachnoid haemorrhage and ARDS. A retrospective study

Abstract: Patients with higher Hunt and Hess grades of subarachnoid haemorrhage who are predominantly intubated and ventilated and most of them suffer from ARDS can receive lung protective ventilation. In our small patient collective, the occurring hypercapnia did not influence (increase) the intracerebral pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…As a conclusion, the treatment reported in the paper by Petridis and colleagues [6]-even if there are really interesting aspects, especially the potentially neuroprotective role of mild to moderate hypercapnia [8]-cannot generally be recommended until studies with a better design, especially controlled, randomized studies, have confirmed the results.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…As a conclusion, the treatment reported in the paper by Petridis and colleagues [6]-even if there are really interesting aspects, especially the potentially neuroprotective role of mild to moderate hypercapnia [8]-cannot generally be recommended until studies with a better design, especially controlled, randomized studies, have confirmed the results.…”
mentioning
confidence: 87%
“…In my opinion, permissive hypercapnia should to date only be administered in patients with a therapy refractory ARDS in whom advanced methods to reduce hypercarbia-e.g., jet ventilation or interventional lung assist devices-if available-have not been successful, i.e., as a form of an individual treatment attempt. A continuously performed ICP monitoring seems to be mandatory-as performed by the authors in the paper [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several small studies suggest that lung protective ventilation strategies causing mild hypercarbia in patients with elevated ICP may be tolerated [63,64], but more data are needed before this may be considered safe in routine practice. Prone positioning seems to increase ICP [65], although several studies show that a small increase in ICP may be more than offset by dramatic improvements in oxygenation.…”
Section: Lung Injurymentioning
confidence: 99%